Content of Music Lessons and its Organization Requirements - kizi, Rustamjonova Dilkhavas Ravshvnbek (International Journal on Integrated Education, 2023)
The goals and objectives of the "Music culture" lesson in general education schools, teaching methods, requirements set by the state educational standard, ways of organizing lessons based on new pedagogical technologies, and lesson development by classes items are provided.